Confucian philosophy in Soo Cham's Air Mata Ibu - Md Zain, Rosnani; Nik Muhamad Affendi, Nik Rafidah (Dewan Bahasa dan Pustaka, 2019)
This article aims to analyse elements of Confucian philosophy in Soo Cham's novel, Air Mata Ibu. The research was carried out based on the understanding that literature is not merely beautiful but also heavily-infused with an all-encompassing philosophy of life that is to be conveyed to the reader. Therefore, this article attempts to explore Confucian philosophy in this novel by the Chinese-Malaysian writer, Soo Cham (2007). The findings of this study show that the ren, zhi, yi, and li concepts of Confucian philosophy, as well as the importance of education, can be applied in human life and are found in this novel.